Purchasing and supply chain management - Monczka, Robert M (Boston, MA : Cengage Learning, 2016)
Summary:Providing a solid managerial perspective, this text draws from the authors' firsthand experiences and relationships with executives and practitioners worldwide to present the most current and complete coverage of today's supply management process. The text includes critical developments from the field, such as cases from emerging healthcare and service industries, procure-to-pay redesign, supply risk, innovation, sustainability, collaboration, and much more.
Includes bibliographical references and index.
Keywords: Purchasing; Industrial management